Retraction: Rendon-Marin et al. Canine Morbillivirus from Colombian Lineage Exhibits In Silico and In Vitro Potential to Infect Human Cells. Pathogens 2021, 10, 1199 - Santiago Rendon-Marin; Carolina Quintero-Gil; Diego Guerra; Carlos Muskus; Julian Ruiz-Saenz (Pathogens, 2022)
The authors retract the article “Canine Morbillivirus from Colombian Lineage Exhibits In Silico and In Vitro Potential to Infect Human Cells” [...]